Dissociated neural signals of conflict and surprise in effortful decision Making: Theta activity reflects surprise while alpha and beta activity reflect conflict. (14th May 2021) - Williams, Chad C.; Ferguson, Thomas D.; Hassall, Cameron D.; Wright, Bruce; Krigolson, Olave E.
Abstract: What makes a decision difficult? Two key factors are conflict and surprise: conflict emerges with multiple competing responses and surprise occurs with unexpected events. Conflict and surprise, however, are often thought of as parsimonious accounts of decision making rather than an integrated narrative. We sought to determine whether conflict and/or surprise concurrently or independently elicit effortful decision making. Participants made a series of diagnostic decisions from physiological readings while electroencephalographic (EEG) data were recorded. To induce conflict and surprise, we manipulated task difficulty by varying the distance between a presented physiological reading and the category border that separated the two diagnoses. Whereas frontal theta oscillations reflected surprise – when presented readings were far from the expected mean, parietal alpha and beta oscillations indicated conflict – when readings were near the category border. Our findings provide neural evidence that both conflict and surprise engage cognitive control to employ effort in decision making. Highlights: Conflict and surprise concurrently characterize effortful decision making. . Parietal alpha and beta band activity reflected conflict signals. Frontal theta band activity reflected surprise signals. There exists dissociable neural measures of conflict and surprise.